PENERAPAN MODEL PEMBELAJAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 025 SEKELADI KECAMATAN TANAH PUTIH - Nur’Aini Nur’Aini; Lazim N Lazim N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : this Research is backgrounded to back by its low of result study IPS with average class that is 62,50. whereas the value that to be decided to value of completing minimum (KKM) that is 70. research sabjek this is student III SDN class 025 Sekeladi with student's number 16 people. this research is be executed to month January until month April Year Teachings 2014/2015. this Research is the class action research that have go to to to level it result study class student IPS III SDN 025 Sekeladi with to apply it the cooperative studying model Two's Type Stay Two Stray (TSTS). data collection Instrument to this skripsi is the activity observation sheet teacher and student, this Matter can to be proofed with the activity obtaining value teacher to cycle first meetings first s is 62,5% with enough category, and second s meeting 71,87% with Good category. to cycle second meetings first to level become 81,25% with category Very Good, and second cycles meeting second s is 84,37% with category Very Good. To activity observation first cycles meeting first s 62,5% with enough category, and second s meeting 68,75% with Good category. To meeting first cycles second s 78,12% with Good category, and to meeting second s 87,5% with category Very Good. result Leveling study student can be seen from base skor with average 62,50% with category don't finish, whereas first cycle average 72,50 with category finish, and to cycle second average 82,18 with category finish. Result showed that the Cooperative Studying Model-Implement Two Stay Type Two Stray (TSTS) can to level it result study class student IPS III SDN 025 Sekeladi, the White Soil .Keyword: the Cooperative Studying Model Type Two Stay Two Stray (TSTS). Process and Result Study